Diseño de un sistema de espacios públicos a través de la revitalización de vacíos urbanos en la parroquia Caranqui de la ciudad Ibarra - Palma Paredes, Jordan Aldair (2023)
The graduation project focuses on the design of an open space system in the parish of Caranqui, located in Ibarra. It presents a unique opportunity to revitalize and take advantage of the existing urban voids in this community. These urban voids, which refer to unoccupied or underutilized lands or areas in the urban fabric, ofer signifcant potential to transform them into vibrant and multifunctional public spaces that meet the needs of residents and promote social interaction. The use of urban voids in Caranqui will allow the creation of green areas, squares, and parks that encourage recreation, leisure, and community coexistence. These open spaces will ofer a respite amid the built environment, providing inhabitants a place to relax, carry out outdoor activities, and enjoy a natural environment. In addition, the design of the open space system should be inclusive and accessible to all residents, taking into account the needs of people of all ages and abilities. Pedestrian paths, play areas, rest zones, and suitable urban furniture can be incorporated to ensure user comfort and convenience. Information was collected about projects that took advantage of urban voids in other cities by reviewing topics related to our project. This allowed us to obtain a more complete and systematic understanding of their performance. Through the study methodology, we were able to identify the successes and errors of previous projects. With this information in mind, we selected and evaluated efective methods for inclusion in the development of work and used evaluation methods for abandoned spaces to categorize them with the help of methods from other authors. The creation of an architectural infrastructure in Caranqui is proposed with the aim of establishing a nucleus that integrates recreational, commercial, banking, and cultural spaces. This proposal arises as a response to the concentration of commercial areas in a single place in the parish, which tends to be the only site visited by tourists